2013
DOI: 10.1021/ac3030448
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharide Analysis of Glycosaminoglycans Using Hydrophilic Interaction Chromatography and Mass Spectrometry

Abstract: Heparan sulfate (HS) and chondroitin sulfate/dermatan sulfate (CS/DS) glycosaminoglycans (GAGs) participate in many important biological processes. Quantitative disaccharide analysis of HS and CS/DS is essential for the characterization of GAGs and enables modeling of the GAG domain structure. Methods involving enzymatic digestion and chemical depolymerization have been developed to determine the type and location of sulfation/acetylation modifications as well as uronic acid epimerization. Enzymatic digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 48 publications
5
65
2
Order By: Relevance
“…A likely explanation for this phenomenon is anomeric interconversion. Similar findings have been reported previously [13]. These authors found that interconversion between the α and β forms occurred with one form predominating at increased temperature.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 4 more Smart Citations
“…A likely explanation for this phenomenon is anomeric interconversion. Similar findings have been reported previously [13]. These authors found that interconversion between the α and β forms occurred with one form predominating at increased temperature.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Depolymerization can be achieved using specific lyases which cleave the glycosidic linkage between a hexosamine and a hexuronic acid thus introducing an unsaturated bond (absorbing at 232 nm) between the C4 and C5 of the hexuronic acid. GAGs can also be depolymerized chemically by mild hydrazinolysis and subsequent deaminative cleavage with nitrous acid [13]. This method retains the original epimeric nature of the hexuronic acid but loses information about the N-sulfation or N-acetylation because the resulting disaccharide comprise a hexuronic acid linked to a 2,5-anhydrohexose bearing an aldehyde group [13].…”
Section: Imeobongmentioning
confidence: 99%
See 3 more Smart Citations